Challenging the Notion of the East‐West Memory Divide*. (23rd April 2019) - Toth, Mano
Abstract: Recent scholarly works on memory practices in Europe often appeal to the notion of the East‐West memory divide or, more dramatically, to the European memory wars which have been allegedly raging at least since the Eastern enlargement of 2004. These terms are supposed to stand for the heated debate between the East and the West, between the countries on the opposing sides of the former Iron Curtain, about what the appropriate memory for Europe should be. In this article, I challenge this simplistic division and I argue that it completely disregards the role of agency. In contrast, I conduct an agent‐centred empirical analysis and show that the social actors involved in the debate are far more diverse, the fault lines are far less clear and the sides of the debate are far more heterogeneous than the carelessly used notion of the East‐West memory divide would have us believe.